(untitled) (Journal of Engineering, 2010)
Thermohydraulic computer codes such as COBRA3C are now becoming in practical use as part of power plant licensing process. One of the areas of interest to reactor designer is the effect due to longterm operations and the changes that might occur either due to irradiation (burnup) effects or thermal stresses in the reactor. The present study is an attempt to predict coolant channel temperature profiles at the core End Of Life. In addition deeper insight is given to the individual single partial contribution to the changes in Begin Of Life and End Of Life profiles. The effects due to fuel swelling, rod bowing, and changes in physical properties are studied in details using COBRA3C code. The codes COBRA3C and the kinetic code AIREKMOD together a structure routine are joined in a modular system. As a result coupling between the different transient parameters in normal and abnormal operation conditions could be performed. Results of such coupling are shown to improve the prediction of DNBR.